Comparison of obstetric outcomes with use of two different standard doses of oxytocin for induction of labor - Gupta, Alka; Thakare, Rucha; Prasad, Madhva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The interventions used in a suspected abnormal labor include amniotomy (artificial rupture of membranes), oxytocin infusion, forceps application and caesarean section. No study is available for individualised treatment with oxytocin. Considering the literature review, many unanswered questions remain regarding the use of oxytocin and definite improvements are possible. All this led us to choose this as the topic for study. Methods: This study was conducted over a duration of 18 months (January 2017 to June 2018) where ninety (90) laboring patients admitted in a tertiary care hospital were included. They were categorized into two groups, one group (30 patients) received the low dose and the other group (60 patients) received high dose oxytocin infusions. The labor outcomes including the maternal and fetal outcomes were observed. Results: The average age in the study population was 26 years and the average gestation was 38 weeks. The overall rate of cesarean section in this study was 16.67% (23.33% in the low dose group and 13.33% in the high dose group). Gravidity and parity have an association with the vaginal delivery. Conclusions: It is safe to use oxytocin infusion either in the low dose or the high dose for induction of labor as both the regimens are equally effective and comparable in terms of outcomes. The low dose oxytocin regimen can be safely recommended in a patient requiring oxytocin infusion for induction of labor and the treating doctor should consider starting with low dose oxytocin.